Mutations in Growth-Related Genes Induced by EMS Treatment in Scallops - Wang, Caihui; Liu, Bo; Chen, Min; Ning, Junhao; Lu, Xia; Wang, Chunde (Frontiers in Genetics, 2022)
Background: The goal of genetic breeding is to select variants with mutations that are related to expected traits, such as fast growth. Artificial induction has been widely used to obtain strains with more mutations for further selection. Ethylmethylsulfone (EMS) is one of the most commonly used chemical mutagens in plant and microorganism breeding. However, the application of EMS mutagenesis in shellfish has not been reported. The aim of this study is to evaluate the potential use of EMS as a mutagen in scallop breeding, especially in characterization of mutations in growth-related genes. Results: Our results indicated that hatching of about 50% of fertilized eggs was blocked by treatment with 20mM EMS for 3 h and the resulted larvae developed normally into adult stages. We then evaluated the mutagenic effects of EMS by sequencing the genomes of 4 adult scallops from the control group and 12 from the treatment group at 8 months after fertilization. On average, after removing shared types of mutations, there were 1151380±258188 SNPs and 229256±51714 InDels in each animal in the EMS treatment group, while there were only134841±10115 SNPs and 42605±5136 InDels in the control group. The average mutation rate in the genome of the EMS treatment group (0.0137±0.0013%) was about 9 times that of the control group (0.0015±0.0002%). GO annotation and KEGG enrichment analyses revealed that mutations induced by EMS occurred evenly in most biological processes, cellular components and functions, as well in most pathways. However, significant lower percentage of mutations were found in the exonic region, in non-synonymous or Stopgain/Stoploss SNPs and in coding domains, suggesting apparent DNA repair or selection during grow-out stage. Analyses of the growth-related genes with mutations indicated that mutations in MFS and Tubulin were only found in the large-sized group (Five largest scallops: Treated-1, Treated-2, Treated-3, Treated-4 and Treated-5) and Homeobox and Socs only in the small group (Two smallest scallops: Treated-11 and Treated-12). These results suggested that these genes may be involved in the regulation of growth in these animals, although further verification is certainly warranted.